MANIFESTASI LOGIKA SEBAGAI DASAR MANUSIA BERNALAR - Amir, Johar; Budiharsono, Andi (SOSCIED, 2023)
Logic is a branch of philosophy that discusses about rules, principles, laws and methods or procedures for achieving knowledge rationally and correctly, It is also a way to gain knowledge by using thoughts, words and language systematically. Logic can be systematized into There are several groups of things depending on which perspective we see that in terms of quality, logic can be distinguished into two, namely naturalist logic (natural logic) and logic artificialist (scientific logic). The aim of this research is to describe the ability to think Manifestation of Logic as the basis for human reasoning. Problem formulation: how to describe the ability to think Manifestation of Logic as the basis for human reasoning?. The method used in this research is a qualitative method with a descriptive approach, the way to obtain data is in the form of a literature study. The results of this research are that the stages of scientific activity require tools in the form of means of thinking, scientific manifestation of logic. The logic of scientific thinking only functions as a tool for humans to think scientifically in order to obtain knowledge. Language is a means of communicating a systematic logical way of thinking in acquiring knowledge. The results of the research are deductive logical thinking and inductive logic as well as the five basic laws of logic. It is needed to support correct scientific thinking activities so that it will produce knowledge with correct logic